Correspondence between thermal biology and locomotor performance in a liolaemid lizard from the southeastern coastal Pampas of Argentina. (April 2022) - Dematteis, Agostina; Stellatelli, Oscar Aníbal; Block, Carolina; Vega, Laura Estela; Dajil, Juan Esteban; Cruz, Félix Benjamín
Abstract: The behavioral and physiological mechanisms of thermoregulation and the morphological traits of lizards result in a particular range of body temperatures, which influence performance and ultimately fitness. We studied the thermal biology and locomotor performance of the lizard Liolaemus wiegmannii from the coastal dunes in the southeastern Pampas of Argentina. During the austral summer, we examined the link between thermoregulation and optimal locomotor performance. Liolaemus wiegmannii faced a stressful environment due to high risk of overheating; despite this, the species was able to achieve field body temperatures (Mean T b ± SD = 35.58 ± 2.86 °C) than expected by chance (i.e., the null model) and suitable for sustaining its physiological performance. Locomotion in this species was thermally-sensitive, with lizards showing high-performance bouts at a relatively wide range of body temperatures (30–38 °C). Lizards exhibited a mean maximum running speed of 1.30 m/s at 37.3 °C (i.e., optimal temperature for locomotion) which was within the set point range of preferred temperature ( T set = 35.4–37.5 °C). Therefore, we found a correspondence between thermal optimum and preferred temperature. Our findings suggest that L. wiegmannii, like other lizard species with a broad distribution, is capable of performing well across a wide range of temperatures despite the spatiotemporal thermal fluctuations of the environment. Highlights: We inquired the link between thermoregulation and locomotor performance in a lizard. Individuals avoided operative temperatures close to the critical thermal maximum. Thermal optimum, preferred temperature and field body temperature converged. High thermoregulatory efficiency enables maximal locomotor performance in the field. This enhances the responsiveness of Liolaemus wiegmannii to the environment.